Multiple primary melanoma in association with other personal and familial cancers. (5th August 2022) - Yang, Xi; Karapetyan, Lilit; Huang, Ziyu; Knight, Andrew D.; Rajendran, Sneha; Sander, Cindy; Minnier, Christopher P.; Wilson, Melissa J.; Kirkwood, John M.
Abstract: Background: Multiple primary melanoma (MPM) is known to be associated with familial melanoma. However, the association between MPM and other personal and familial cancers is not well documented. The objective of this study was to evaluate the association between MPM and personal history of other cancers or cancer history among first‐degree relatives (FDRs). Methods: We performed a retrospective case–control study including cases with gender‐matched MPM and single primary melanoma (SPM) at a 1:2 ratio from the University of Pittsburgh Cancer Institute Melanoma Center Biological Sample and Nevus Bank. The associations between MPM and other cancers were evaluated using univariable and multivariable logistic regression models. Results: In total, 378 patients (44.2% men; median age 52 years) were enrolled, including 252 with SPM and 126 with MPM. In comparison to patients with SPM, patients with MPM were more likely to have squamous cell carcinoma (odds ratio [OR] 1.95, 95% confidence interval [CI] 1.001–3.79, p = 0.047) and prostate cancer (OR 2.72, 95% CI 1.07–7.01, p = 0.034). FDRs of patients with MPM had higher prevalence of melanoma (OR 2.37, 95% CI 1.31–4.28, p = 0.004) and prostate cancer (OR 2.92, 95% CI 1.47–6.14, p = 0.002) but not other cancers. In multivariable analysis, the association remained significant between MPM and squamous cell carcinoma (OR 2.18, 95% CI 1.08–4.39, p = 0.028), prostate cancer (OR 2.85, 95% CI 1.09–7.54, p = 0.032), FDR history of melanoma (OR 2.37, 95% CI 1.31–4.29, p = 0.004), and FDR history of prostate cancer (OR 3.26, 95% CI 1.59–6.83, p = 0.001). Conclusions: Patients with MPM have a higher prevalence of personal and FDR histories of nonmelanoma skin cancers and prostate cancer. Abstract : This retrospective case–control study enrolled patients ( n = 378) with multiple primary melanoma (MPM) and single primary melanoma (SPM) at a 1:2 ratio and evaluated the association between MPM and other cancers using logistic regression models. Compared with patients with SPM, patients with MPM were more likely to have squamous cell carcinoma (OR 1.95, 95% CI 1.001–3.79, p = 0.047), basal cell carcinoma (OR 1.66, 95% CI 0.99–2.74, p = 0.051), and prostate cancer (OR 2.72, 95% CI 1.07–7.01, p = 0.034).